Completing Self-Administered Questionnaires: Hmong Older Adults and Their Family Helpers - Lor, Maichou (Field methods, 2019)
This study describes a method for collecting data from non-literate, non-English speaking populations. Our Audio computer-assisted self-interview instrument with color-labeled response categories was designed for use with a helper assistance. The study included 30 dyads of non-literate older Hmong respondents and family helpers answering questions about health. Analysis of video recordings identified respondents’ problems and helpers’ strategies to address these problems. Seven dyads displayed the paradigmatic question-answer sequence for all items, while 23 departed from the paradigmatic sequence at least once. Reports and pauses were the most common signs of problems displayed by respondents. Paraphrasing questions or response categories and providing examples were the most common helper strategies. Future research could assess the impact of helpers’ strategies on data quality.